Graphical User Interface (GUI) for Torsional Vibration Analysis of Rotor Systems Using Holzer and MatLab Techniques - Nassar, Ameen Ahmed (Basrah Journal for Engineering Sciences, 2014)
In this study, a new approach for the torsional vibration analysis of rotor systems using Holzer and Matlab techniques, by developing a graphical user interface (GUI), has been introduced. The objective of the work is to show the usefulness and power of Matlab GUI in investigating and analyzing the effects of torsional vibration on rotor systems. Also to carry out an analysis using the developed GUI to simulate three different rotor configurations such as 2-Rotor, 3-Rotor, and 5-Rotor systems. Illustrated problems in the field of analysis of torsional vibration are carried out. The results show that the developed GUI is very useful for engineers, designers, and analysts of torsional vibration problems in rotor systems.